PENDAMPINGAN BELAJAR TEKNIK DASAR PERMAINAN SEPAK BOLA BAGI SISWA SDI RUTOSORO KECAMATAN GOLEWA - Bernabas Wani; Yovinianus Mbede Wea; Nikodemus Bate; Yanuarius Ricardus Natal; Yohanes Bayo Ola Tapo; Robertus Lili Bile; Filemon Darmanto Ndora (Jurnal Abdimas Ilmiah Citra Bakti, 2022)
This Community service is motivated by students whose ability to learn bacic soccer game tecnicques is still low due to lack of basic soccer game technical training. Therefore, the purpose of community service in providing assistance to basic techniques of soccer games for Rutosoro Inpres elementary school. This can be seen when observing the Rutosoro Elementary School. It can be seen that student cannot do well the basic techniques of soccer games, as the basic for the learning theme of the big ball game which aims to improve students physical fitness and skills in soccer game technical and tactics as an effort to in crease students activity. Learning mentoring activities also aim to regenerate the enthusiasm of students who declined during the Covid-19 pandemic. The method used in the tutoring activities is the direc practice method in the field with the basic material of the basic technic of playing soccer with training procedures, namely warming up, core activities and cooling down, in the core material, an explanation of the basic tecnick that have been explained by the service activity assistant.